+0  
 
0
151
1
avatar
ln 7 + ln (n - 2) = ln 6n
Guest Apr 13, 2012
Sort: 

1+0 Answers

 #1
avatar+3071 
0
ln( 7 ) + ln (n - 2) = ln( 6n)
with: ln( x*y ) = ln(x)+ln(y)

ln ( 7 * (n-2) ) = ln( 6n )
e^x on both sides (if n>0)

7 * (n-2) = 6n
7n - 14 = 6n
7n - 6n = 14
n = 14
admin  Apr 13, 2012

19 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details